Eksistensi Hak Ulayat Pasca Berlakunya Peraturan Menteri Agraria Nomor 18 Tahun 2019 - Wimba Roofi Hutama (Notaire, 2021)
The Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia recently issued Ministerial Regulation of ATR No. 18 of 2019 concerning Procedures for Administration of Customary Land Community Units of Customary Law. However, the reality is that until now there are still ulayat lands of customary law community units whose management, control and use are based on local customary law provisions and are recognized by the members of the customary law community unit concerned. The research uses normative research, namely normative juridical research, namely research based on applicable laws and legal norms and has binding power to answer the legal issues faced. The results obtained are that the characteristics of customary rights of customary law communities, that customary rights to land are controlled by customary law communities, namely people who live in groups, hereditary based on ties of origin/ancestor or similarity of residence, have the same culture, live in a certain area, have customary property that is jointly owned, have customary institutions containing sanctions, as long as they are still alive according to developments and do not conflict with national law.Keywords: Existence; Customary Rights; Minister of Agrarian Regulation.Menteri Agraria Dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia baru-baru ini menerbitkan Permen ATR No. 18 Tahun 2019 Tentang Tata Cara Penatausahaan Tanah Ulayat Kesatuan Masyarakat Hukum Adat. Namun kenyataannya hingga kini masih terdapat tanah ulayat kesatuan masyarakat hukum adat yang pengurusan, penguasaan dan penggunaannya didasarkan pada ketentuan hukum adat setempat dan diakui oleh para warga kesatuan masyarakat hukum adat yang bersangkutan”. Penelitian dengan menggunakan penelitian normatif, yaitu penelitian yuridis normatif, yaitu penelitian didasarkan peraturan perundang-undangan atau norma-norma hukum yang berlaku dan mempunyai kekuatan mengikat guna manjawab isu hukum yang dihadapi. Diperoleh hasil bahwa Karakteristik hak ulayat masyarakat hukum adat, bahwa hak ulayat atas tanah tersebut dikuasai oleh masyarakat hukum adat, yakni masyarakat yang hidup berkelompok, turun menurun berdasarkan ikatan asal usul/leluhur atau kesamaan tempat tinggal, berbudaya sama, hidup dalam satu wilayah tertentu, memiliki harta benda adat milik bersama, mempunyai pranata adat mengandung sanksi, sepanjang masih hidup sesuai perkembangan dan tidak bertentangan dengan hukum nasional.Kata Kunci: Eksistensi; Hak Ulayat; Peraturan Menteri Agraria.